Is The Learning Curve In Robotic Assisted Laparoscopic Radical Prostatectomies (RALP) in South Africa Comparable to International Standards? - de Jager, Simon (Division of Urology, 2020)
Background and purpose Prostate cancer (PCa) is the second most common cancer in men, and the sixth leading cause of cancer death among men worldwide (1). Radical Prostatectomy (RP) is widely considered a gold standard treatment for clinically significant localized PCa. Robotic assisted laparoscopic radical prostatectomy (RALP) represents a modern minimally invasive technique for performing a RP. The aim of the study is to demonstrate a progression in the learning curve of two South Africa based urologists, as each embarks on their first series of RALP cases between September 2014 to July 2019. An audit of peri-operative outcomes for each surgeon's first uninterrupted series of RALP's has been undertaken. We also compare our results to international series to assess if local South African outcomes are similar to these. Materials and Methods We performed a retrospective audit of all patients who had a RALP with our two urologists between the dates of September 2014 to May 2019. Patients were only excluded if critical data could not be collected. For each included patient we collected peri-operative data. Pre-operative data collected was required for risk stratification grouping of patients according the D'Amico Risk group classification. Post-operative data included operative details (such as console time and blood loos), functional outcomes (such as potency and continence rates), and pathological outcomes (such a T-staging and positive surgical margin rates). The total number of patients for each of the two surgeons have been divided into a series of consecutive groups. The first 100 have been divided into groups of 25, and the subsequent patients into groups of 50. Results/main findings Our two surgeons have been designated Surgeon-X and Surgeon-Y. A total of 700 patients met our inclusion criteria, 400 and 300 cases for Surgeons-X and -Y respectively. Our study demonstrates that in a South Africa setting, for the parameters of median console time (CT), estimated blood loss (EBL), length of hospital stay (LOS), and positive surgical margins (PSM), there were notable improvements between the first and last groups of each surgeon's series. Although each parameter tends to fluctuate around a median value, there is a general trend towards improved outcomes. For the parameters of post-operative continence and potency our study failed to show a statistically significant improvement in outcomes between the first and last groups in each surgeon's series. Conclusions This study demonstrates that, similar to internationally published data, notable improvements in perioperative outcomes can be observed as each of our two surgeons gain experience in this relatively new operative approach to managing men with localized prostate cancer. The overall picture is one of improved outcomes with each consecutive group analysed and that when individually assessed, these outcomes display differing rates of improvement depending on which is being assessed. When analysing our outcomes of CT, EBL, PSM rate and LOS, we see that our results compare favourably to other internationally published data. For all intents and purposes our learning curve and peri-operative results are on par with our overseas counterparts and in some cases bette